2023
DOI: 10.11591/ijece.v13i2.pp1979-1988
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid approach based on personality traits for hate speech detection in Arabic social media

Abstract: <p>In recent years, as social media has grown in popularity, people have gained the ability to freely share their views. However, this may lead to users' conflict and hostility, resulting in unattractive online environments. Hate speech relates to using expressions or phrases that are violent, offensive, or insulting to a minority of people. The number of Arab social media users is quickly rising, and this is being followed by an increase in the frequency of cyber hate speech in the area. Therefore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…While previous research has explored various methodologies for hate speech detection, there still needs to be more consensus on the most efficient and accurate algorithmic combinations. Individual methods, such as support vector machines (SVM) (e.g., Elzayady et al, 2023) or recurrent neural networks (RNN) (e.g., Mazari & Kheddar, 2023), have been studied in previous research. However, a comprehensive comparative analysis of multiple algorithms is necessary to determine the optimal combination that balances accuracy, simplicity, computational efficiency, and ease of implementation.…”
Section: Research Articlementioning
confidence: 99%
“…While previous research has explored various methodologies for hate speech detection, there still needs to be more consensus on the most efficient and accurate algorithmic combinations. Individual methods, such as support vector machines (SVM) (e.g., Elzayady et al, 2023) or recurrent neural networks (RNN) (e.g., Mazari & Kheddar, 2023), have been studied in previous research. However, a comprehensive comparative analysis of multiple algorithms is necessary to determine the optimal combination that balances accuracy, simplicity, computational efficiency, and ease of implementation.…”
Section: Research Articlementioning
confidence: 99%
“…Challenges in hate speech detection on social media have been acknowledged, emphasizing the complexity of identifying and addressing hate speech online (Kovács et al, 2021). The offensive and insulting nature of hate speech has been linked to personality traits, suggesting a hybrid approach for hate speech detection in Arabic social media (Elzayady et al, 2023). In summary, hate speech on social media, particularly in the context of Indonesia, presents a multifaceted challenge that requires a combination of technological solutions, legal frameworks, and societal interventions to effectively combat its spread and impact.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning techniques have emerged as a promising solution, offering sophisticated feature representation and learning capabilities [7]. Studies leveraging Convolutional Neural Networks (CNNs) have demonstrated success in text classification and offensive content detection, owing to their ability to capture hierarchical text features [8]. Separately, Long Short-Term Memory (LSTM) networks, a form of recurrent neural networks (RNNs), have proven effective in understanding sequential data, thereby interpreting the context within the text efficiently [9].…”
Section: Introductionmentioning
confidence: 99%